MATHEMATICAL MODELING OF CALCULATION OF SPATIAL STRUCTURES UNDER VARIABLE LOADS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The technology for calculating the stress-strain state of elastoplastic bodies with a cavity or a cavity, using the developed software, is based on the ideas of algorithmization, computational experiment and modular programming.